Resistance Functions for Two Spheres in Axisymmetric Flow—Part I: Stream Function Theory - Thanaa El Naqeeb; Rudi Schmitz (Journal of Applied Mathematics)
We consider low-Reynolds-number axisymmetric flow about two spheres using a novel, biharmonic stream function. This enables us to calculate analytically not only the forces, but also the dipole moments (stresslets and pressure moments) and the associated resistance functions. In this paper the basics properties of axisymmetric flow and the stream function are discussed. Explicit series expansions, obtained by separation in bispherical coordinates, will be presented in a follow-up paper.